A STUDY OF THE COMPONENTS OF FACTORS RELEVANT TO THE ADMINISTRATIVE INTEGRITY OF KERMAN᾽S TECHNICAL AND VOCATIONAL TRAINING HEAD OFFICE - Mohammadi, Majid; Salajegheh, Sanjar; Sayadi, Saeed (Revista Inclusiones, 2019)
In governmental organizations, administrative integrity leads to proper ideas, decision-makings and executing the policies appropriately and thereby, resulting in efficient and effective public services. Various elements play a role in administrative integrity. They are including: individual, organizational, political, social, economic, cultural and legal elements. Accordingly, present study aimed to investigate the dimensions and components of the factors relevant to administrative integrity in one of the governmental organizations called Kerman Technical and Vocational Training head office. The present study was descriptive and exploratory research and the data were collected by library method and field study. The statistical population of present study includes all the official and casual members (n=400) of the organization studied and 196 of them were selected as research samples using the Morgan table. For the dimensions of factors relevant to the administrative integrity, the reliability of the questionnaire was estimated 0.89 using Cronbach's alpha. Then, factor analysis and principal component method were used to determine the dimensions of the factors related to the administrative integrity and seven key factors were identified through the exploratory analysis. These factors were confirmed again through the confirmatory factor analysis. In present paper, statistical analyses were used using SPSS23 and AMOS23 software. According to the confirmatory factor analysis, all the fitting indices of the model were confirmed. Moreover, it was found that there is a significant differences between heads, deputies and employees in the average responses of some dimensions.